Primary lesion location influences postoperative survival in patients with metastatic colorectal spinal lesions. (March 2016) - Goodwin, C. Rory; Sankey, Eric W.; Liu, Ann; Abu-Bonsrah, Nancy; Elder, Benjamin D.; Rhee, Jay; Kosztowski, Thomas; Bydon, Ali; Witham, Timothy F.; Wolinsky, Jean-Paul; Gokaslan, Ziya L.; Sciubba, Daniel M.
Highlights: Pain was the common presenting symptom for patients with colorectal spinal metastases. Patients with spinal metastasis from rectal primary lesions have longer survival than patients with colon primary lesions. Surgery for colorectal spinal metastases may be associated with a high incidence of perioperative complications. Abstract: Spinal metastasis from colorectal cancer occurs rarely. However, with increasing incidence of colorectal cancer in the setting of improved therapies, physicians are more likely to encounter such patients. We performed a retrospective review of patients who underwent spine surgery for metastatic colorectal cancer from 2005–2011. Preoperative, operative and postoperative factors; functional outcome as determined by Karnofsky Performance Status (KPS) and modified Rankin scale (mRS); and survival were recorded. Univariate analysis was performed, with patients stratified into two groups based on the position of the primary cancer, either proximal (colon) or distal (rectum) to the rectosigmoid junction. Fourteen patients, with a median age of 52 (interquartile range [IQR] 48–66) years, underwent 21 spine surgeries for metastatic colorectal cancer. Pain was the common presenting symptom (n = 11, 79%), followed by motor weakness (n = 8, 57%). Twenty-seven postoperative complications occurred in 11 (52%) patients. Baseline KPS and mRS remained stable in four (29%), improved in two (14%), worsened in six (43%), and was unknown in two (14%) at last follow-up. Patients with spinal metastasis from a rectal primary (n = 6) had a significantly longer survival compared to those with a colon primary (n = 8), with a median survival of 84 (IQR 56–103) versus 26 (IQR 19–44) months after primary diagnosis (p = 0.002), 19 (IQR 13–27) versus five (IQR 3–9) months after spine metastasis diagnosis (p = 0.010), and six (IQR 4–14) versus three (IQR 2–4) months after surgery (p = 0.030). Patients with spinal metastasis arising from rectal primary lesions display longer survival compared to colon lesions. Consideration of these factors is essential to appropriately assess surgical candidacy.